The family man : blood and betrayal in the house of Murdaugh - Lasdun, James (W.W. Norton & Company, 2026)
"In March of 2023, Alex Murdaugh was found guilty of murdering his wife Maggie and their younger son Paul at Moselle, their home in South Carolina's Lowcountry. By then the story had become headline news across the country, with its revelations of corruption in high places, massive fraud, opioid abuse, fake suicides, suspicious accidents, and the generational recklessness of the wealthy legal dynasty at its center. Featuring a cast of villains ranging from supposedly respectable bankers and lawyers to violent street gang members, the story has, not surprisingly, been the subject of several books and TV shows already. But few have focused on the enigma of Alex Murdaugh himself as brilliantly as James Lasdun's The Family Man. Having covered the case for the New Yorker, where his article became the magazine's most read story of 2023, the acclaimed novelist brings his long-standing interest in the darker drives of the human psyche to an investigation into the serial embezzlements, fatal boat crash and other events leading up to the slaughter at Moselle. Having traveled extensively in the Lowcountry interviewing people involved in the case (including Murdaugh's notorious 'Cousin Eddie') and attending hearings with Murdaugh himself, Lasdun looks at Murdaugh through a series of revelatory perspectives that include recordings of Murdaugh's jail conversations, the literature of criminal psychology, and the murder trial itself, to create a masterful portrait of his subject and an immersive account of the psychological and social processes by which a seemingly loving family man became a 'Family Annihilator.'"-- Provided by publisher.